Pengaruh Diskon, Gratis Ongkos Kirim, dan Pembayaran COD (Cash On Delivery) Cek Dulu terhadap Keputusan Pembelian pada E-Commerce Shopee - Hadiyasin, Prastyo Nova; Widarko, Agus; Slamet, Afi Rachmat (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of discounts, free shipping, and COD (Cash On Delivery) Check First payment on purchasing decisions in Shopee e-commerce. This research employs a quantitative approach with an explanatory research design. The study sample consists of 100 respondents selected using the accidental sampling technique. Data were collected through an online questionnaire and analyzed using multiple regression analysis. The results indicate that discounts, free shipping, and COD Check First payment have a positive and significant influence on purchasing decisions. These findings imply that e-commerce platforms like Shopee can optimize their marketing strategies by maintaining and enhancing these three factors to encourage consumer purchasing decisions. Keywords: Discount, Free Shipping, COD Check First, Purchase Decision, E-commerce